Personnel Economics essay: Issues in Human Capital Theory, training and earnings of workers - Dushko Josheski (ZBW - Deutsche Zentralbibliothek für Wirtschaftswissenschaften, Leibniz-Informationszentrum Wirtschaft, 2014)
In this paper the issues from the personnel economics has been investigated. The issues such as training of workers from Becker's human capital theory and their association with the workers' productivity. In the second part of the paper the issue of grooming has been investigated in relation with earnings for which there exist and it is presented empirical evidence. In the equation as regressors are also present Mincerian variables: age, marital status and others. Also the four puzzles in the empirical literature about the determinants of earnings has been investigated. And how the empirical literature helps in resolving them.
Keywords: M50; M52; M53; 650; Personnel economics; training; earnings; grooming